2020
DOI: 10.3389/fvets.2020.582297
|View full text |Cite
|
Sign up to set email alerts
|

Survey and Sequence Characterization of Bovine Mastitis-Associated Escherichia coli in Dairy Herds

Abstract: Escherichia coli is frequently associated with mastitis in cattle. “Pathogenic” and “commensal” isolates appear to be genetically similar. With a few exceptions, no notable genotypic differences have been found between commensal and mastitis-associated E. coli. In this study, 24 E. coli strains were isolated from dairy cows with clinical mastitis in three geographic regions of Australia (North Queensland, South Queensland, and Victoria), sequenced, then genomically surveyed. There was no observed relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…coli and mastitis associated E. coli has occurred; however as with our study no metadata was collected to explain the pathway of transmission, for example, through movement of cattle from one farm to another [14, 44].…”
Section: Discussionmentioning
confidence: 99%
“…coli and mastitis associated E. coli has occurred; however as with our study no metadata was collected to explain the pathway of transmission, for example, through movement of cattle from one farm to another [14, 44].…”
Section: Discussionmentioning
confidence: 99%
“…Herd selection was based on ease of access to the farm location and the cooperation of the dairy farm owners and their associated veterinary practices. Detailed methodology is described elsewhere 101 . Briefly, milk samples were collected from eligible dairy cows with a new case of clinical mastitis.…”
Section: Methodsmentioning
confidence: 99%
“…This study has predicted the sequence type, evolutionary phylogeny, ARGs, VFGs, and genomic metabolic potentials of the isolates of E. coli from MT and FS. The findings of our research shed light on genetic relatedness of E. coli which is known as a predominant pathogen in mammalian mastitis [ 16 , 23 , 62 , 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our investigation of the genomes also revealed the presence of three CRISPR arrays in each genome harboring 12 signature genes. CRISPR arrays, which have been identified in many bacterial pathogens (including E. coli ) causing mastitis, play a significant role in host adaptive immune response and virulence [ 66 ]. The genomic data from this study showed that the E. coli isolate from MT (G2M6U strain) was genetically distinct from the one from FS (G6M1F strain) in murine mastitis.…”
Section: Discussionmentioning
confidence: 99%